KEBIJAKAN PEMERINTAH INDONESIA DALAM MENANGANI PENYEBARAN KASUS COVID-19 - Nurian Endah Dwi S; Aidinil Zetra; Roni Ekha Putera (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2023)
This paper aims to see how the government's policies in preventing and dealing with the growth of positive cases of Covid-19 in Indonesia. The method used is a qualitative method, with the focus of the study on government policies related to handling Covid-19, both at the beginning of the spread in 2020 until the case of the spread of Covid-19 in 2022. The results of the study show that government policies to prevent the spread of transmission of the Covid-19 virus in Indonesia, continues to experience changes. Until 2022, there are 4 additional government policies in handling Covid-19 cases in Indonesia.